Dynamics of Revenue Generation in Tanzania, Kenya and Uganda: A Co-integration and error-correction modeling approach - Mwakalobo, Adam B. S. (African Journal of Economic Review, 2015)
The dynamics of revenue generation in Tanzania, Kenya and Uganda are explored. Results demonstrate that revenue generation is sluggish in Tanzania compared to Kenya and Uganda. Macroeconomic environment, economic structure, and level of development are fundamental at explaining these differences. Results reveal that these countries have the potential for generating more revenue, if could address weaknesses inherent in their tax systems. Computerization of tax collection; expansion of the tax base; address problems associated with tax revenue leakages; and instituting strong legal enforcements should be at the fore in the ongoing tax reforms so as to enhance tax revenue collection.